Study the effect different layer arrangement on efficiency of gallium arsenide solar cells: article / Meor Mohd Ekhwan Meor Ibrahim - Meor Ibrahim, Meor Mohd Ekhwan (2009)
This research was conducted to study the effect of different layer arrangement of GaAs p/n heteroface solar cell. Three different model of GaAs p/n heteroface solar cell structure were introduced and had been simulated. The analysis focused on spectral response analysis. From spectral response analysis, two parameters were issue, photo current and efficiency. The final result shows that, different layer arrangement can effect on photo current and efficiency.